A rare case of invasive pulmonary aspergillosis presenting as organizing pneumonia due to Aspergillus niger in an immunocompetent host. (2021) - Schils, Raphaël; Altdorfer, Antoine; Moerman, Filip; Weber, Thierry; De Waele, Michèle; Maertens, Johan; Pirotte, Benoit F.
Abstract: Invasive pulmonary aspergillosis associated with organizing pneumonia is increasingly described and mainly affects the immunocompromised individual. Most of Aspergillus invasive infections in both immunocompetent and immunocompromised patients are attributed to Aspergillus fumigatus. Herein we describe a clinical case of pulmonary Aspergillus niger infection presenting as an organizing pneumonia in an immunocompetent patient. A wedge resection and two successive cures of azoles (voriconazole 6 weeks then itraconazole 6 weeks) were necessary for the patient to be totally recovered. The association of OP and IPA is rare. The involvement of A. niger makes it even rarer, this is the reason why we decided to report on this case.